2019
DOI: 10.5713/ajas.18.0920
|View full text |Cite
|
Sign up to set email alerts
|

Unique epithelial expression of S100A calcium binding protein A7A in the endometrium at conceptus implantation in pigs

Abstract: Objective S100A7A, a member of the S100 protein family, is involved in various biological processes, including innate immunity, antimicrobial function, and epithelial tumorigenesis. However, the expression and function of S100A7A in the endometrium during the estrous cycle and pregnancy are not well understood in pigs. Therefore, this study determined the expression and regulation of S100A7A at the maternal-conceptus interface in pigs. Methods We obtained endometrial ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In humans, the expression of PI3 peaks during menstruation, and the expression of SLPI peaks during the late secretory phase of the menstrual cycle [ 10 , 15 ]. We previously reported that several AMPs, such as the cathelicidin family [ 22 ], the S100 family [ 23 , 24 ], and the beta-defensin family (Lee and Ka, unpublished data), are also differentially expressed in the endometrium during the estrous cycle and at the maternal–conceptus interface during pregnancy in pigs. In this study, we found that PI3 and SLPI are expressed in the endometrium throughout the estrous cycle and pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the expression of PI3 peaks during menstruation, and the expression of SLPI peaks during the late secretory phase of the menstrual cycle [ 10 , 15 ]. We previously reported that several AMPs, such as the cathelicidin family [ 22 ], the S100 family [ 23 , 24 ], and the beta-defensin family (Lee and Ka, unpublished data), are also differentially expressed in the endometrium during the estrous cycle and at the maternal–conceptus interface during pregnancy in pigs. In this study, we found that PI3 and SLPI are expressed in the endometrium throughout the estrous cycle and pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…During pregnancy, the amount of calcium in the uterine endometrial tissue increases, and calcium deposits are made at the site where the embryo implants in the uterus. These are critical steps for the onset of pregnancy [45,369,370]. The hormone estrogen has been identified as a factor that increases the uptake of calcium in the body and influences the activity of specific genes [371,372] in the endometrium that are crucial for the initiation of pregnancy [45,369,370].…”
Section: Calciummentioning
confidence: 99%
“…These are critical steps for the onset of pregnancy [45,369,370]. The hormone estrogen has been identified as a factor that increases the uptake of calcium in the body and influences the activity of specific genes [371,372] in the endometrium that are crucial for the initiation of pregnancy [45,369,370]. Among the significant genes related to uterine function and development is the Homeobox A10 (HOXA10) gene [373].…”
Section: Calciummentioning
confidence: 99%
“…Because the expression of SAA3 in the endometrium was greatest on Day 12 during pregnancy and implanting porcine conceptuses secrete estrogen and cytokines, IL1B and IFNG, we postulated that the conceptus-derived estrogen and cytokines would increase endometrial SAA3 expression. Estrogen of conceptus origin is responsible for inducing the expression of many endometrial genes, such as aldo-keto reductase 1B1, fibroblast growth factor 7, IFN-alpha and beta receptor subunit 2, IFNG receptor beta subunit, lysophosphatidic acid receptor 3, S100A7A, S100A8, and secreted phosphoprotein 1 [1,3,28]. IL1B and IFNG also increase the expression of many endometrial genes involved in PG synthesis and transport and immunity, respectively [1].…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…In mice and humans, SAAs synthesized from intestinal epithelial cells act as opsonins that activate phagocytes by binding to outer membrane protein A of bacteria, and they also show antimicrobial activity [7]. Our previous studies have shown that the maternal endometrium and conceptus tissues during pregnancy in pigs produce a variety of antimicrobial peptides (AMPs), including cathelicidins [31], S100A7A [28], S100A8, S100A9, S100A12 [32], β-defensin family, peptidase inhibitor 3, and secretory leukocyte protease inhibitor (Lee and Ka, unpublished data). Therefore, our results in this study suggest that SAA3 expressed at the maternal-conceptus interface acts as a component of endometrial and choriallantoic AMPs that protect implantation sites from possible contamination by microorganisms and maintain fertility during pregnancy.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%